THE ROLE OF URBAN CENTERS IN DRIVING ECONOMIC DEVELOPMENT IN UZBEKISTAN - Dilshod Khaydarov (Journals Park Publishing, 2025)
Cities are the epicenters of economic, technological, and cultural progress in the modern world. This article analyzes the economic significance of urban centers, with a focus on Uzbekistan, and explores how urbanization contributes to national development. Using qualitative and comparative methods, the article identifies key infrastructure, labor market, and innovation dynamics that drive city economies. It concludes that efficient urban planning and strategic investment are essential for balanced and sustainable development.
Keywords: Urban economy, urbanization, infrastructure, city development, economic growth, labor markets, Uzbekistan, innovation, regional balance.